Echocardiographic Profile of Patients with Cardiomyopathy - Khanal, Jeevan; Pandy, Tilchan; Godar, Krishna (Journal of Lumbini Medical College, 2018)
Introduction: Cardiomyopathies represent a heterogeneous group of diseases that often lead to progressive heart failure with significant morbidity and mortality. Exact epidemiological data on cardiomyopathy in Nepal are lacking. This study was done to observe the demographic and echocardiographic profile of patients with cardiomyopathy attending a medical college teaching hospital. Methods: Trans-thoracic two-dimensional echocardiographic study was performed by first author on all patients with cardiomyopathy over a period of six months. Patients’ demographic and echocardiographic data were collected and analyzed using SPSS version 20 software. Student t-test and Chi-square test were applied where appropriate. Results: A total of 60 patients were studied from October 2017 to March 2018. Mean age of all participants was 56.38 years (SD = 13.86). Mean age of males was significantly higher than that of females (60.96 yrs, SD = 13.61 versus 51.62 yrs, SD = 13.47) in dilated cardiomyopathy subgroup (p < 0.05). Of all patients, 32 (53.33%) had dilated cardiomyopathy (idiopathic) and 13 (21.66%) had ischemic cardiomyopathy. Conclusion: Our study highlighted significant burden of dilated cardiomyopathy. Dilated cardiomyopathy appeared in females at earlier age compared to males. Potentially reversible cardiomyopathies like alcoholic and peripartum cardiomyopathies were also present which have a probability of cure if treated properly. DOI: https://doi.org/10.22502/jlmc.v6i2.255